O rozwiazywaniu dwuwymiarowych zagadnień teorii naprężeń cieplnych - Filipkowski, J. (Engineering Transactions, 1968)
Some particular two-dimensional problems of the theory of thermal stresses are discussed in the present paper. They are the problem of stress distribution in a semiinfinite plate subject to the action of a concentrated source of heat and the same problem for an infinite plane with an elliptic hole acted on by two concentrated sources of heat one positive, the other negative. These problems are considered for various boundary conditions. In conclusion are given some remarks on the solution of other problems of the theory of thermalstress. In the case in which the temperature function is discontinuous along a closed contour the solution method of the problems considered is discussed in detail. All the considerations are based on the relations given in Refs. [2 and 3].